Drugs misuse in Malaysia: past and present - Kamarudin, Abdul Rani (2007)
This paper gives a historical insight, how drugs first came to be commercially introduced into South East Asia including Malaysia, and the early measures taken to control and regulate their use. It also explains the origin of their use in Malaysia to a stage when it became cancerous to the country requiring the government to take drastic measures to combat them. Accordingly, this paper primarily discusses the Dangerous Drugs Act 1952 which is foremost statute on dangerous drugs laws of Malaysia, and the Malaysian government's stance or policy over the misuse of narcotic drugs.